CAMPANHAS ELEITORAIS SUSTENTÁVEIS: O PAPEL DA INOVAÇÃO NO CUMPRIMENTO DOS OBJETIVOS DE DESENVOLVIMENTO SUSTENTÁVEL: SUSTAINABLE ELECTION CAMPAIGNS: THE ROLE OF INNOVATION IN ACHIEVING THE SUSTAINABLE DEVELOPMENT GOALS - Cavalcanti Ramos Machado, Raquel; Farias de Vasconcelos, Anna Sara (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2026)
ABSTRACT – The change from in-person rallies to printed materials for digital networks reduces the impacts on the natural and urban environment, reducing noise pollution and waste production, and also makes it possible to increase social inclusion and transparency during the electoral campaign. However, this digitalization process presents other challenges, namely: the possible increase in misinformation and computer exclusion, requiring the creation of effective and inclusive regulations. In addition, it is important to think of joint paths to promote sustainable campaigns, in a dialogue between institutions, parties, candidates and citizens. The methodology used was bibliographic research, based on scientific materials, which already carefully explore the subject. This work aims to analyze how technological innovation can influence the organization of the electoral process, specifically, the change in the way of conducting electoral campaigns, whose purpose should be the adoption of innovation in conjunction with the sustainable development goals (SDGs), so that the various types of environment, including the digital environment, are respected. The results indicate that a more sustainable electoral campaign benefits everyone in general. It is concluded that the exercise of electoral propaganda, in the forms permitted by law, constitutes a clear and certain right of the candidate and also a diffuse right of society, which must remain informed in order to make the right choices. Keywords: Electoral campaigns. Innovation. Resolution. Sustainability.